DESIGN AND BUILD A CLEAN WATER SERVICE INFORMATION SYSTEM (CASE STUDY OF THE DOWN CIASEM VILLAGE) - rahayu, slamet; Dania, Dania (Universitas Lampung, 2020)
AbstractPAMSIMAS in Hilir Ciasem Village has customers that include residents of Hilir Ciasem Village. In managing customer data, the calculation of bills and payment of water bills are now still done manually. The purpose of this research is to build a web-based information system with PHP programming language and MySQL database as data storage. The design method in this study uses the System Development Life Cycle (SDLC) waterfall model. A clean water service information system is produced that can store data, manage customer data, and make payments easily. Testing is done using the Blackbox and UAT methods given to 3 respondents. The test results showed that the application is running as expected with a 100% success rate for Blackbox testing and 82% for the average UAT testing value. It showed that this application can overcome existing problems related to clean water services in PAMSIMAS Hilir Ciasem Village, Subang district. Keywords: Information Systems, Services, Websites, PAMSIMADOI: http://dx.doi.org/10.23960/jpvti.v2.i2.202005